Islamic Perspective in Administering the Covid-19 Vaccine to Children: A Literature Review - Santika, Aprilia Puteri; Hilmawati, Febriana; Ayu Safitri, Putri Gita; Al Hanafi, Yoeri Rafiqi; Suryaman, Sulistia (Walidem Institute and Publishing, 2024)
Vaccines are the best way to tackle the virus outbreak because vaccines can reprogram immunity systems to create their antibodies The vaccine is unlikely to be initially available to children. The risk of children spreading the virus is not zero, and a surge of cases in the community will be reflected in children as well. The policymakers will also consider all other potential benefits against the risks of vaccination in children. Muslims are obliged to consume only halal products. Vaccines needed to follow halal standardization to be used in Islamic countries. This study has the purpose of observing the connection between halal and vaccines in research. This study uses papers indexed in the Scopus website as secondary data. There are two kinds of data, based on the organization of co-authorship, and co-occurrence of authors’ topic. There are 46 numbers of data, including the organization of co-authorship or where the authors affiliated and 68 of co-occurrence of authors’ topic. The data is analyzed using Vosviewer software. The result shows that the topic of vaccines has a connection to halal and fatwa/ or ulama council’s statement. Thus, no Muslim countries such as the USA and Australia have more relevant points than Muslim countries. It can be concluded that halal and vaccine are intertwined with each other, especially in Muslim countries. Halal is not only related to vaccines based on the result above but also has a connection to other topics such as fatwa, Islamic marketing, developing countries, Islam and acceptance. Halal and vaccines have vast varieties of sub-topics to be developed in studies. Based on the keywords in the papers, non-Muslim countries such as the USA and Australia have more relevant points in the study about halal and vaccines. There are vaccine perceptions from society, things related to halal, as well as things related to COVID-19.